Structural Integrity Analysis of the Rig Mast Following Repair of Two Diagonal Braces in the Upper Mast Section - Padmodwiputra, Rendhatya; Soedarsono, Johny Wahyuadi; Mahendra, Mirza; Satria, Bambang Eka; Arif, Chandra; Suarthana, Eka Juni (UI Scholars Hub, 2023)
During a move to the new drilling location, two braces of the upper mast section on a 550 HP oil and gas rig was damaged. When damage is discovered, the rig operating company should conduct a risk analysis related to the damage using the standard used to determine rejection criteria and follow-up repairs. The strength of the rig mast is calculated using Finite Element Analysis (FEA) with initial conditions (before damage occurs) where all braces are installed and extreme conditions where neither brace is repaired. The calculation results are then used to assess the risk of reducing the rig mast strength. The results of the integrity analysis will show FEA of rig mast and the distribution pattern of stress ratio values, which is the ratio between the stress that arises and the allowable stress of the material on the mast parts due to loading.